Application of community dialogue approach to prevent adolescent pregnancy, early marriage and school dropout in Zambia: a case study - Ireen Zamanga Zulu; Joseph Mumba Zulu; Joar Svanemyr; Charles Michelo; Wilbroad Mutale; Ingvild Fossgard Sandøy (BMC, 2022)
Plain language summary Adolescent pregnancy carries health and economic risks for the pregnant girl and her baby. However, many adolescent girls in Zambia become pregnant and this is partly due to social norms around fertility and marriage. Community dialogue meetings may be useful in order to discuss norms and beliefs around early pregnancy, marriage and school dropout and encourage reflection around cultural practices in the communities. A cluster randomized controlled trial in rural Zambia tested the effects of organizing community dialogue meetings and providing economic support for families with adolescent girls for a period of 27 months, from 2016 to 2018. The objective of this case study was to understand parents' perspectives on the use of the community dialogue approach. Focus group discussions were held in November 2018 with guardians/parents in six schools in Chibombo District of Central Province. The guardians/parents perceived the community dialogue to be a relevant approach for addressing social and cultural norms regarding early pregnancy, marriage and school dropout. The facilitators' interactive approach in the community meetings coupled with the use of films and role plays, lead to active participation and open discussions about sexual and reproductive health topics during the community dialogue meetings. Group interactions and sharing of experiences made the guardians feel able to communicate about sexual and reproductive health issues with their children. However, cultural and religious beliefs among the parents regarding the use of condoms and contraceptives made it difficult for them to touch upon this topic.